Training attention in children with acquired brain injury: a study protocol of a randomised controlled trial of the TALI attention training programme - Vicki Anderson; Erin McKay; Sally Richmond; Hannah Kirk; Cathy Catroppa; Kim Cornish (BMJ Open)
Introduction Childhood inattention has been linked with poor academic outcomes, and increased lifetime social, occupational and psychiatric morbidity. Children with an acquired brain injury (ABI) are particularly susceptible to attention deficits and may benefit from interventions aimed at enhancing attention. The primary objective of this study is to evaluate the short-term efficacy of the TALI Train programme, compared with a placebo, on the outcome of attention in children with ABI.Methods and analysis The study is a parallel, double-blind, randomised controlled trial. Participants will consist of 80 children with a diagnosis of ABI aged 4–9 years 11 months. Participants will be randomly allocated to either (1) TALI Train (intervention group), an adaptive game-based attention training programme, or (2) a non-adaptive placebo programme (control group). Both programmes are delivered on a touchscreen tablet, and children complete five 20 min sessions per week for a 5-week period at home. Assessment of selective, sustained and executive attention (primary outcomes), and behavioural attention, working memory, social skills and mathematics ability (secondary outcomes) will occur at baseline, post-training, and at 3-month and 6-month follow-up to assess immediate and long-term efficacy of TALI Train compared with placebo. Assessments will be completed at the Royal Children’s Hospital in Melbourne, Australia. All assessments and analyses will be undertaken by researchers blinded to group membership. Latent growth curve modelling will be employed to examine primary and secondary outcomes.Ethics and dissemination Ethics approval has been obtained from the Royal Children’s Hospital Human Research Ethics Committee (HREC) (38132) and the Monash University HREC (17446). Results will be disseminated through peer-reviewed journals, conference presentations, media outlets, the internet and various community/stakeholder activities.Trial registration number ACTRN12619000511134.